Peer Mediated Instruction and Intervention (PMII) type Classwide Peer Tutoring (CWPT) and Academics Ability of Natural Science-Biology in Vocational High School - Hamsiah Hamsiah (Jurnal Pendidikan Sains, 2013)
Peer Mediated Instruction and Intervention (PMII) tipe Classwide Peer Tutoring (CWPT)dan Kemampuan Akademik pada Pembelajaran IPA Biologi SMK Abstract: Learning science in SMK 1 Bontang still dominated by conventional learning strategy is a method of learning with lecture. This has an impact on learning outcomes of cognitive science that tends biology is still low because the students have not been trained become independent learners, thus learning innovation PMII CWPT types can be used as a breakthrough to develop the cognitive learning. This study was conducted to determine the application CWPT strategies and academic skills in science teaching vocational Biology. Quasi-experimental research with pretest-posttest design Nonequivalent Control Group. Results of the study, namely: (1) there CWPT effect on the cognitive learning, (2) no influence academic ability to cognitive learning outcomes, and (3) there is no interaction effect between learning strategy and the academic ability toward the cognitive learning. Key Words: peer-mediated instruction and intervention, classwide peer tutoring, academic skills, cognitive learning outcomes Abstrak: Pembelajaran IPA di SMKN 1 Bontang masih didominasi dengan strategi belajar konvensio-nal yaitu metode belajar dengan ceramah. Hal ini berdampak terhadap hasil belajar kognitif IPA biolo-gi yang cendrung masih rendah karena siswa belum terlatih menjadi pebelajar yang mandiri, sehingga inovasi pembelajaran PMII tipe CWPT dapat digunakan sebagai terobosan untuk mengembangkan  hasil belajar kognitif. Penelitian ini dilakukan untuk mengetahui penerapan strategi CWPT dan kemam-puan akademik pada pembelajaran IPA Biologi SMK. Penelitian eksperimen semu dengan rancangan pretest-posttest Nonequivalent Control Group. Hasil penelitian, yaitu: (1) ada pengaruh CWPT ter-hadap hasil belajar kognitif,  (2) ada  pengaruh  kemampuan akademik terhadap hasil belajar kognitif, dan (3) tidak ada  pengaruh interaksi antara strategi pembelajaran dan kemampuan akademik terhadap  hasil belajar kognitif.Kata kunci: peer mediated instruction and intervention, classwide peer tutoring, kemampuan aka-demik, hasil belajar kognitif